Studies on Costa Rican Vanilloideae : the return of Cleistes rosea and a reaffirmation of Epistephium ellipticum - Karremans Lok, Adam Philip
Subfamily Vanilloideae represents a small fraction of the orchid flora of Costa Rica, and yet our knowledge of this predominantly South American group has significantly increased in the last two decades. Until recently, Vanilloideae was represented in Costa Rica by just two genera: Cleistes and Vanilla, with one and seven species respectively. Today, up to 13 species of Vanilla are shown to occur in the country, we evidence the presence of a second species of Cleistes and confirm the presence of a third genus Vanilloideae in Costa Rica: Epistephium. The rare Cleistes rosea and Epistephium ellipticum are fully illustrated on the basis of Costa Rican materials with Lankester Composite Digital Plates (LCDP). The typification of Cleistes rosea is discussed and a color illustration is provided of C. costaricensis for comparison.